2015
DOI: 10.1039/c5ob01451d
|View full text |Cite
|
Sign up to set email alerts
|

Differential detergent sensitivity of extracellular vesicle subpopulations

Abstract: a Extracellular vesicles (including exosomes, microvesicles and apoptotic bodies) are currently attracting rapidly increasing attention from various fields of biology due to their ability to carry complex information and act as autocrine, paracrine and even endocrine intercellular messengers. In the present study we investigated the sensitivity of size-based subpopulations of extracellular vesicles to different concentrations of detergents including sodium dodecyl sulphate, Triton X-100, Tween 20 and deoxychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
170
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 21 publications
9
170
0
6
Order By: Relevance
“…Finally, loss-of-function assays will help exclude other sources of bioactive molecules in the exosomes preparation. These assays include UV irradiation (to destroy RNA in exosomes) or mild detergent treatment, which either obliterates the effect of exosomes (if based on RNA) or exosomes themselves (Coumans et al, 2017; Kinoshita et al, 2017; Osteikoetxea et al, 2015). Our group has specialized on pre-purification loss-of-function assays by preventing formation or secretion of exosomes in vitro and in vivo (Dinkins, Dasgupta, Wang, Zhu, & Bieberich, 2014; Dinkins, Enasko, et al, 2016; Kong, Hardin, et al, 2015; G.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…Finally, loss-of-function assays will help exclude other sources of bioactive molecules in the exosomes preparation. These assays include UV irradiation (to destroy RNA in exosomes) or mild detergent treatment, which either obliterates the effect of exosomes (if based on RNA) or exosomes themselves (Coumans et al, 2017; Kinoshita et al, 2017; Osteikoetxea et al, 2015). Our group has specialized on pre-purification loss-of-function assays by preventing formation or secretion of exosomes in vitro and in vivo (Dinkins, Dasgupta, Wang, Zhu, & Bieberich, 2014; Dinkins, Enasko, et al, 2016; Kong, Hardin, et al, 2015; G.…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…The use of TRIzol© for the isolation of nucleic acids from cells and EVs has been well established [11]; however, its utility for protein capture is less well investigated and has not been validated in the context of EVs. While work from the group of Edit Buzas [12] demonstrates differential detergent sensitivity of EV sub-populations, a similar effect was not anticipated with the TRIzol© protein-extraction reagent because TRIzol© (or Laemmli) extraction does not depend on this principle. The main barrier to using TRIzol© for protein recovery arises from poor reproducibility and difficulty in the re-solubilization of the protein pellet from the prescribed acetone- or isopropanol-mediated precipitation step [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies employing detergents reported on the stability of exosomes. [27][28][29] It would be interesting to compare the effects of detergents on the membrane integrity of exosomes prepared from various sources.…”
Section: Effect Of Detergents On Salivary Exosome Stabilitymentioning
confidence: 99%